MINDS@UW: a digital institutional repository service - Southworth, Heidi; Malzacher, Valerie (My University, 2006)
In spring 2005, Chalmer Davee Library took the first steps towards sponsoring a presence for the University of Wisconsin-River Falls in the MINDS@UW project. MINDS@UW is a digital institutional repository service that is intended to provide a "safe haven" for published and unpublished electronic content of any discipline and is designed to capture, store, index, distribute and preserve the intellectual output of the university. By August 2005, the Library had posted its first collection to the site. Working in collaboration with the University?s Office of Grants & Research, this first collection consisted of undergraduate student and faculty posters from the 2005 Research, Scholarly and Creative Activity Day (RSCA day). Now, the Library is taking the next step towards establishing more collections within the MINDS@UW project and invites you to offer feedback and discuss with us your questions on this exciting new service.
Color poster with text describing the efforts of Heidi Southworth and Valerie Malzacher from the University of Wisconsin-River Falls' Chalmer Davee Library to establish a presence for the University in the MINDS@UW project. The poster provides a general overview of institutional repositories and the MINDS@UW project.
Keywords: University of Wisconsin-River Falls; Institutional repositories; Scholarly electronic publishing; Institutional repository; Libraries and electronic publishing; MINDS@UW; DSpace; Scholarly publishing--Technological innovations; Chalmer Davee Library; Libraries and scholars; Digital libraries; Information management